RÜŞVET SUÇUNDA SORUŞTURMA VE KOVUŞTURMA USULÜ - (:unkn) unknown (My University, 2015)
Kamu idaresinin güvenirliğine ve işleyişine karşı işlenen suçlardan biri olan rüşvet suçu son yıllarda ülkemizde ve dünyada oldukça yaygınlaşmış ve büyük bir sorun haline gelmiştir. Kamu görevlilerinin görevlerinin ifasıyla ilgili işlerde görev ve yetkilerine aykırı davranarak menfaat temin etmesi, devlete olan güveni azaltmakta ve toplumdaki adalet duygusunu zedelemektedir. Bu nedenle çalışmamızda rüşvet suçunun soruşturma ve kovuşturma usulü ile bu suça ilişkin yaptırım incelenecektir.

Bribery, one of the crimes against the reliability and functioning of public administration has become widespread in recent years in our country and the world and has become a major problem. Public officers to provide benefits by acting contrary to the duties and powers related jobs in the execution have reduce confidence in the State and undermines the sense of justice in society. Therefore, our study will examine the sanctions procedure with the investigation and prosecution of bribery offenses.
(THE INVESTIGATION AND PROSECUTION OF BRIBERY OFFENSE)
Keywords: Hukuk